Study on Simultaneous Determination of Halogen Compounds and Sulfur Oxides in Flue Gas by Using Ion Chromatography - Nonomura Makoto; Kurita Keiko (Challenges and Advances in Chemical Science Vol. 1, 2021)
For the determination of anions, ion chromatography (IC) is a suitable analytical method. Bromine, fluorine, chlorine (Cl2), and hydrogen chloride (HCl) are all included in JIS as analytical procedures for halogen compounds in flue gas. IC, with the exception of HCl and Cl2, has not been adopted in JIS. Because the carbon dioxide in flue gas is absorbed in a 0.1 M sodium hydroxide solution as an absorber, it is interfered with the measurement of F- and Cl- ions. The development of IC’s pretreatment equipment for flue gas analysis, as well as its applications to real flue gas analysis, are described in this study. Using the pretreatment apparatus, theF-, Cl-, Br- and SO42- in the absorbing solution may be clearly separated by IC. IC can simultaneously determine halogen chemicals and sulphur oxides in real flue gas. This method has been adopted to Japanese Industrial Standard (JIS K 0105, JIS K 0085).